Structure of the promoter region for the rrnB gene in Escherichia coli. - Csordás-Tóth, E (1979)
The nucleotide sequence of the promoter region for the rrnB gene of E. coli had been determined by the Maxam-Gilbert technique. The 700 bp long sequence had been compared with the published sequences of four other rRNA promoter regions. The rrnB sequence was found to be homologous with the rrnA promoter sequence till the 370th base upstream from the coding region of mature 16S rRNA. The significance of this homology is discussed and a tentative model is proposed to account for the unusual properties of the rRNA promoters.